Cyclic di-GMP regulates bacterial colonization and further biocontrol efficacy of Bacillus velezensis against apple ring rot disease via its potential receptor YdaK - Gong, Huiling; Jiang, Wenxiao; Yang, Yang; Zhang, Yue; Chen, Xufei; Li, Wei; Yang, Panlei; Wang, Zhenshuo; Wang, Qi; Li, Yan (Frontiers in Microbiology, 2022)
Bacillus species are among the most investigated beneficial bacteria and widely used in agricultural systems as biological control agents. Its biocontrol efficacy is controlled by diverse regulators. Cyclic diguanylate (c-di-GMP) is a nearly universal second messenger in bacteria and modulates various important physiological processes, including motility, biofilm formation, antifungal antibiotic production and host colonization. However, the impact of c-di-GMP on biocontrol efficacy of beneficial bacteria is unknown. Bacillus velezensis PG12 is an effective biocontrol strain against apple ring rot disease caused by Botryosphaeria dothidea. In this study, the contribution of c-di-GMP to biocontrol efficacy of B. velezensis PG12 was investigated. Deletion of single gene encoding diguanylate cyclase or phosphodiesterase did not affect its biocontrol efficacy against apple ring rot. However, artificial modulation of c-di-GMP level in the cells leads to a significant change of biocontrol efficacy, suggesting that c-di-GMP positively regulates biocontrol efficacy of B. velezensis PG12 against apple ring rot disease. More evidences indicate that c-di-GMP does not affect the antagonistic activity of B. velezensis PG12 against B. dothidea in vitro and in vivo, but positively regulates biofilm formation of B. velezensis PG12 and its colonization on apple fruits. Importantly, deletion of ydaK could rescue the inhibition of biofilm formation, bacterial colonization and biocontrol efficacy caused by low c-di-GMP level, indicating that YdaK is the potential c-di-GMP receptor to regulate biofilm formation, colonization and effective biological control. However, YdaK did not affect the antagonistic activity of B. velezensis PG12 against B. dothidea. Based on these findings, we propose that c-di-GMP regulates biofilm formation, subsequently the bacterial colonization on apple fruits and thus biocontrol efficacy of B. velezensis through its receptor YdaK. This is the first report showing that c-di-GMP plays a role in biocontrol efficacy of beneficial bacteria.